Guidelines for the management of dermatomycosis (2019). Issue 12 (25th September 2020) - Mochizuki, Takashi; Tsuboi, Ryoji; Iozumi, Ken; Ishizaki, Sumiko; Ushigami, Tsuyoshi; Ogawa, Yumi; Kaneko, Takehiko; Kawai, Masaaki; Kitami, Yuki; Kusuhara, Masahiro; Kono, Takeshi; Sato, Toshiki; et al.
Abstract: The "Guidelines for the management of dermatomycosis" of the Japanese Dermatological Association were first published in Japanese in 2009 and the Guidelines Committee of the Japanese Dermatological Association revised it in 2019. The first guidelines was prepared according to the opinions of the Guidelines Committee members and it was of educational value. The revised version is composed of introductory descriptions of the disease concepts, diagnosis, medical mycology and recent advances in treatment, along with clinical questions (CQ), which is intended to help in general practice for dermatologists. The CQ are limited to those involved in therapy but include some of the recently launched antifungal agents. The level of evidence and the degree of recommendation for each item were reviewed by the committee based on clinical studies published by 2018. For rare dermatomycoses, recommendations by the committee are described in the guidelines. In this field, there are still few good quality studies on treatment. Periodic revision in line with new evidence is necessary.